ASSESSMENT OF PHYTOTOXICITY OF PHOSPHORUS-CONTAINING WASTE FOR TEST PLANTS (Experimental biology, 2022)
Annotation. Man-made industrial wastes that pollute the environment and cause serious consequences for the sustainability of the biocenosis in it include phosphorus-containing wastes. When assessing the toxicity of man-made waste by biological methods, various groups of hydrobiontic organisms are used as test organisms: microalgae, protozoa, molluscs, plants, etc. Two types of phosphorus-containing waste are used, slag and sludge. A and B, differing in their quantitative and qualitative characteristics. Phaseolus vulgaris, Hordeum vulgare were used as a phyto-test of plants. It was found that the morphometric parameters of the analyzed test plants decreased in proportion to the content of phosphorus-containing wastes in aqueous suspensions.
Keywords: hydrobiontic organisms; biotests; slag; sla; sludge